Can the Sequence of Food Presentation Influence Postprandial Glycaemia? (P10-072-19). (13th June 2019) - Henry, Christiani; Sun, Lijuan; Govindharajulu, Priya; Leow, Melvin Khee-Shing
Abstract: Objectives: The study was to investigate how a rice-based meal composed of rice, vegetable (green leaf) and meat (breast of chicken) when presented in different order of sequence, impacts on postprandial glycaemia. Methods: In a randomized controlled crossover trial, sixteen healthy Chinese adults participated in this study (13 males and 3 females). Subjects consumed in random order 5 experimental meals. The 5 test meal were: (1) vegetables first followed by meat and rice (V-MR), (2) meat first followed by vegetables and rice (M-VR), (3) vegetables first, meat second followed by rice (V-M-R), (4) vegetables, meat and rice together (VMR), (5) rice followed by vegetables and meat (R-VM). Vegetable consumed first followed by meat and rice (V-MR), finally vegetable consumed first, followed by meat and followed by rice (V-M-R). Results: In comparison to rice consumed first followed by vegetable and meat (R-VM), the overall postprandial glucose response was significantly lower after the consumption of vegetable first, followed by meat and rice (V-MR) or meat first, followed by vegetable and rice (M-VR) or vegetable followed by meat and followed by rice (V-M-R) or vegetable, meat and rice consumed together (VMR). The insulin iAUC (0–60) was significantly lower after V-M-R than M-VR, VMR and R-VM. V-M-R food sequence intake stimulated higher GLP-1 release than other meal sequence. However, GIP response was lower after V-MR and V-M-R than M-VR and R-MR food sequence. Conclusions: Food sequence can considerably influence a meals response to glycaemic, insulinaemic and incretin. V-M-R food sequence intake lowered the glycaemic response significantly with an increased stimulation of GLP1. The order of food presentation has a great potential to alter the glycaemic response of rice-based diets. Our results provide a simple but effective way to reduce postprandial glucose and may help prevent the transition from pre-diabetics to diabetics Funding Sources: Singapore Institute for Clinical Sciences, A*STAR, Singapore. Supporting Tables, Images and/or Graphs: